Coexistence of models of protection in public policy for children in Chile: Towards a rights perspective - Villegas-Alarcón, Valeria Andrea; Reyes-Rodríguez, Alixon David; Venegas-Hernández, Massiel Carolina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
This article reflects on the models of protection that guide public policy on for children in Chile, paying particular attention to the theoretical and epistemological foundations. that support its assessment. From a critical perspective and with a focus on rights, it is argued that evaluation practices should not be understood as exclusively technical procedures, but rather as expressions of conceptual-epistemological constructions that shape ways of interpreting the child as a subject, state action, and public responsibility. It is assumed that that the effectiveness of protection models depends on the coherence and robustness of their theoretical-epistemological frameworks, as well as on the institutional capacity of the state to ensure stable and articulated planning processes, along with consistent implementation that aligns with these frameworks. Given the evidence of instability, discontinuity, and insufficient integration in the policies evaluated, an analytical matrix is proposed that allows to recognize the evaluative rationalities at play and their contribution—or lack thereof—to the construction of a system of protection that is, integral, sustainable, and focused on children and their rights.